Numerical Simulation for Scenario Based Volcanic Hazard Assessment (VHA) at Seulawah Agam Volcano, Aceh, Sumatra - Muhammad Syukri; Amir Fauzi; . Fashbir; . Irwandi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Seulawah Agam is an active volcano with high 1,810 m located at 5.448°N 95.658°E and close to the capital of Aceh province densely populated. Following Sumatra-Andaman earthquake 26 December 2004, Sumatra Island has increased not only seismicity but also volcanic activity. On the other hand, Sinabung volcano categorized as inactive volcano, but beyond expectations on the 3rd September 2010 experienced eruption and the closest volcanic eruption location to Seulawah Agam volcano. Meanwhile, in 1 September 2010, Seulawah Agam categorized as active volcano was alert to level 2. We cannot predict what happens in future to the Seulawah Agam volcano, but we can provide volcano hazard assessment as important step for mitigation procedure. This paper introduces numerical study for volcanic eruption and integrated with a GIS-based tool for volcanic hazard assessment VORIS (VOlcanic Risk Information System) which develop by Alicia Felpeto.  This model investigate scenario based volcanic eruption for ash fallout, PDC (pyroclastic density currents), and lava. Digital elevation model (DEM) from SRTM (Shuttle Radar Topography Mission), meteorological data from NOAA, and geological study are used in this model. In the statovolcano mountain four geothermal manifestations appeared, such as: Fumarol Simpago, crater Heutz, ground steam Ie-Jue, and hot spring Ie-Suum. In this numerical simulation, we consider the location as potential eruption vent to produce erupted material. Wind velocity data at 3rd January 2012 and 1 July 2012 above the summit is selected to represent wet and dry season condition for scenario based ash fallout. Further, the simulation show the ash fallout is possible to reach Banda Aceh and potentially disrupt flight at Sultan Iskandar Muda Air port. Lava flow simulations are only depending on topography data (DEM) and applying some parameter for maximum flow length 5 km. The Simulation resolution depend on DEM data (90m) which produce more precise then volcanic hazard map produce by Center of Volcanology and Geological Hazard Mitigation, Bandung (CVGHM) and more reasonable with topography slope of mountain at southern part and northern part. Furthermore, PDC simulations are conducted scenario for height eruption column (starting point of the flow) 20m dan 200m. The simulations show PDC can be reach longer location until Banda-Aceh Medan Highway compare then CVGHM map.  This preliminary research should be developed to apply high resolution DEM and using adequate method for estimation eruption parameters. This method will be potential to provide more precise volcano hazard assessment for others volcano in Indonesia